Novel case of androgen receptor‐positive cancer of unknown primary without serum prostate‐specific antigen elevation that became progression free in the long term after primary combined androgen blockade. Issue 1 (30th November 2020) - Matsuyama, Nayuka; Naiki, Taku; Naiki‐Ito, Aya; Chaya, Ryosuke; Kawai, Tatsuya; Etani, Toshiki; Nagai, Takashi; Kato, Hiroyuki; Kubota, Yasue; Yasui, Takahiro
Abstract : Introduction: The prognosis of cancer of unknown primary is very poor. Such a prognosis can be improved by characterizing primary characteristics and developing tailored site‐specific therapy, especially for androgen receptor‐positive adenocarcinoma. However, in such cases without elevated prostate‐specific antigen, the efficacy of androgen deprivation therapy is unclear. Case presentation: Herein, we report a case that presented with a retroperitoneal cancer of unknown primary that was confirmed as an androgen receptor‐positive adenocarcinoma without prostate‐specific antigen elevation. Pelvic magnetic resonance imaging did not reveal any suspicious cancer lesions in the prostate. Furthermore, malignant cells were not present in a prostate biopsy specimen. In spite of the prostate‐specific antigen level, on the basis of immunohistochemical analyses, including NKX3.1, the patient was first treated with androgen deprivation therapy, leading to long‐term progression‐free survival. Conclusion: Early androgen deprivation therapy based on immunohistochemical analyses might lead to a good outcome in androgen receptor‐positive adenocarcinoma cancer of unknown primary patients regardless of prostate‐specific antigen level.